VISUALITY, LANGUAGE AND COMMUNICATION IN COVID-19 NIGERIAN SOCIAL MEDIA IMAGES - Maledo, Richard Oliseyenum; Ativie, Karoh (International Review of Humanities Studies, 2023)
Covid-19 is one of the most disturbing infections that has rattled the world in recent history. This flu affected nearly all the countries of the world with different degrees of medical, scientific, social and scholarly attentions. The humanities are not left out from the perspective of language and communication during the pandemic. In the light of the above, this paper undertakes a multimodal semiotic analysis of Covid-19 memes in the Nigerian context with a view to showing how the visual and language complement each other in communicating aspects of Nigerian socio-political realities during the pandemic. Among the images circulated through the Whatsapp medium, ten were selected for this study and Kress and van Leeuween’s (2006) multimodal theory was adopted as our theoretical framework. The findings revealed that language and visual images effectively complement each other as viewers are made to gain easy and quick access to the messages being communicated with a visual understanding of the realities on ground.